Life story as a way of subjectivity expression - Gil Ramírez, Nora Elena (Pensando Psicología, 2010)
Reintroducing data from research conducted by this article’s author in Medellin city, whose main goal is to understand why a woman kills, it illustrates how to investigate using life story. Exploratory, descriptive and explanation moments are shown; the latter involves in-depth analysis that must be followed at methodological level to extract sense and psychic elements operating as cause and through which the subject produces a subjective reality endowed with meaning, which is part of the fabric that allows the researcher understanding of social reality, in this case homicide committed by a woman. Subjectivity is conceived as the system of particular meanings and signifiers emerged from dynamic and trends established among intra-psychic elements with cultural and social processes, as inscriptions and identifications with language and culture where subject moves. We conclude that within life story as subjectivities’ research tool it is not enough that events are represented in a chronological order, but they should be revealed by an structure, by a signifier order absent in the sequence itself.